Bifurcation analysis and integrability in the segmented disc dynamo with mechanical friction - Liu, Y; Li, J; Wei, Z; Moroz, I (Springer Open, 2018)
Using center manifold theory, we investigate complex dynamics in a segmented disc dynamo with mechanical friction by making a determination of equilibrium states and analyzing local stability. We find that the system undergoes Hopf bifurcation for a key parameter. Normal form theory produces the formulae for determining a superor sub-critical Hopf bifurcation; the stability of the bifurcating limit cycle is also determined. In addition, integrability of the system is studied carefully.